Public Service Communication Management in Hajj Administration: A Systematic Literature Review - Desi Hasbiyah; Mumuh Mulyana; Hageem Che-Ni; Kaleem Saleem (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to systematically review and synthesize the existing literature on public service communication management in Hajj administration. Given the complexity of Hajj as a large-scale religious public service involving multiple actors, high regulatory intensity, and diverse service users, communication management plays a critical role in ensuring service effectiveness and public value creation. Using a Systematic Literature Review (SLR) approach guided by the PRISMA framework, this study analyzes 18 peer-reviewed journal articles published between 2010 and 2024 and indexed in major academic databases. The findings reveal that communication management consistently functions as an integrative and strategic capability linking governance, service coordination, and pilgrim experience. Effective communication is strongly associated with key service outcomes, including service quality, satisfaction, trust, and compliance. The review also identifies dominant research themes, commonly used conceptual models, and significant research gaps, particularly the lack of integrative frameworks and empirical testing. This study contributes to the literature by consolidating fragmented research and proposing directions for future empirical and comparative studies. Practically, the findings offer insights for policy makers and service managers to strengthen communication strategies and enhance the quality of Hajj service delivery within complex public service systems. Keywords: public service management; communication management; Hajj administration; service quality; systematic literature review